‘Nobody had their back’: The differentiated deportability of Central and Eastern Europeans in the UK - Radziwinowiczówna, Agnieszka (European journal of criminology, 2025)
This article demonstrates that under the same regulations, some social groups are more vulnerable to deportation than others. It analyses the case of the deportation of EU citizens from the UK before the abandonment of the principle of EU free movement. My analysis of the law?practice continuum includes law-on-the-books (UK legislation) and law-in-action (primary research among deportees, EU migrants, and experts; and the analysis of internet forums, statistics, policy papers and documents obtained through Freedom of Information Requests). Before Brexit, the UK introduced laws, policies, and practices that made possible the deportation of large numbers of EU citizens. Central and Eastern European EU (CEEU) citizens (especially racialised, low- or no-income and working-class men, including Roma people) were disproportionately more likely to be targeted for deportation than citizens of countries that had been members of the EU prior to 2004. This article finds that UK law and practice mobilised crimmigration against CEEU migrants, with criminal and immigration legislation converging to facilitate their expulsion. I describe how the illegalisation and criminalisation of (1) CEEU citizens who had contact with criminal justice system (including prisoners) and (2) CEEU citizen rough sleepers contributed to their deportability. The UK deportation regime took active steps to deport these groups (including by creating the ?abuse/misuse?-of-right policy targeting rough sleepers); the treatment they received from the UK criminal justice system (high sentencing, lack of free legal aid in deportation cases) heightened their deportability. The article concludes that this differentiated deportability of CEEU nationals can be viewed as prefiguring post-Brexit deportation policy in the UK.